A remarkable new palpigrade (Arachnida) of the Eukoenenia mirabilis group from Spain - Mayoral, J.g.; Barranco, P. (Zootaxa, 2017)
Eukoenenia indalica sp. nov. is described from a female captured in a cave in the mountains of Almeria, in Andalusia, southeastern Spain. It belongs to the E. mirabilis group, which includes species found in the Mediterranean region, Macaronesia, the Caribbean and, in one case, worldwide. The new species is unique within this group in showing cave-dwelling traits, especially the elongation of the legs. Its IVbta is the third largest known for a palpigrade, after those of Eukoenenia draco and E. sagarana. The chaetotaxy and metric data indicate that E. indalica sp. nov. is related to local endogean species.